Integrasi Karakter Profil Pelajar Pancasila dalam Perangkat Pembelajaran Calon Guru Bahasa Indonesia - Soleh, Anjas Rusdiyanto; Pratiwi, Dini Restiyanti; Pratiwi, Dini Restiyanti (Prosiding University Research Colloquium, 2021)
The aim of this research is to identify integration of the Profil Pelajar Pancasila in the learning tools of prospective Indonesian teachers. This research uses qualitative research by applying descriptive method. The data sources in this study is learning tools from Microteaching courses student university in Indonesian Language and Literature Education study program, Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta. The data in this research is the form of parts in the learning device which is an integration of the Profil Pelajar Pancasila. Data collection techniques used in this research are note-taking and documentation techniques. Analysis of the data in this study using content analysis techniques. The results of this study indicate that the integration of the six aspects in the Profil Pelajar Pancasila is spread over several types of learning tools in the form of Learning Implementation Plans, Student Worksheets, and assessment or evaluation instruments. By the three types of learning tools, the integration of the Profil Pelajar Pancasila is contained in the learning steps in the Learning Implementation Plans, learning instructions in the Student Worksheets, and in the assessment aspect on assessment or evaluation instrument.